Thirty-six-year trends (1986–2022) in cigarette smoking and snus use in northern Sweden: a cross-sectional study - Stefan Söderberg; Maria Wennberg; Viktor Oskarsson; Jonas Andersson; Erica Sjödin; Maria Nordendahl; Lena Heldorsson Fjellström; Carolina Lundholm (BMJ Open)
Objectives To examine the 36-year trends in tobacco use in northern Sweden.Design and outcome measure Cross-sectional analysis of the eight population-based surveys that constitute the northern Sweden MONICA study (1986, 1990, 1994, 1999, 2004, 2009, 2014 and 2022). Cigarette smoking and snus use were self-reported via questionnaires, and age-adjusted percentages of cigarette smoking (including occasional use) and snus use were calculated via logit models.Setting General population of Norrbotten and Västerbotten (the two northernmost counties of Sweden).Participants 6678 women and 6320 men, aged 25 to 74 years, were included for analysis. A total of 191 participants were excluded due to missing data on either cigarette smoking or snus use.Results Cigarette smoking decreased on a survey-to-survey basis, reaching a minimum in 2022 of 4.9% among men and 9.7% among women, corresponding to a percentage point change of 26.3 and 20.8, respectively, compared with 1986 (pwithin-group<0.01). With respect to snus, the use increased steeply up until 1999 among men, after which it persisted around 25% to 30% (26.2% in 2022), with percentage point changes between 6.6 and 13.4 compared with 1986 (pwithin-group<0.01). The percentage of female snus users was extremely low in the first surveys but increased continuously over time, reaching a maximum of 13.0% in 2022 and a percentage point change of 12.5 since 1986 (pwithin-group<0.01). Cigarette smoking—but not snus use—was more common in Norrbotten than in Västerbotten in 2022 (pbetween-group<0.01).Conclusions A substantial decline in cigarette smoking has occurred over time in northern Sweden, particularly among men and more notably in Västerbotten. In contrast, snus use has become increasingly common in both sexes and in both counties.